Pilot implementation of a sonography simulator in gynecological medical training and continuing education: A practical report - Röhle, Anne; Willemer, Marie-Christin; Birdir, Cahir; Nitzsche, Katharina (GMS Journal for Medical Education, 2024)
Objective: In addition to patient consent, learning sonography requires considerable time and personnel resources. To implement patient-friendly and resource-saving ultrasound teaching, a comprehensively equipped sonography simulator (SoSim) was purchased at the Medical Interprofessional Training Centre (MITZ) of the Faculty of Medicine at TU Dresden. In a first step, the SoSim training was trialed in a sample (n=5) in cooperation with the Clinic and Polyclinic for Gynecology and Obstetrics at Dresden University Hospital (GYN). Based on the findings, the aim is to extend the project to University Medicine Dresden.Description of the project: After creating the necessary structural and organizational conditions, five female GYN trainees trained two defined modules in SoSim on transvaginal and abdominal ultrasound. The evaluation was carried out by online-based evaluation of the participants and process analysis.Results: The process analysis showed that close supervision of the learners is required and that booking individual appointments is time-consuming. The evaluation of the participants showed a positive mean change in the approval ratings for 11 out of 14 competency-based questions.Conclusion: Despite the integrated SoSim learning program, support for learners is necessary. By piloting the use of SoSim to teach transvaginal ultrasound as part of gynecological specialist training, University Medicine Dresden is a pioneer in innovative and patient-friendly teaching. The pilot project has laid the foundations for the expansion of the project into other areas.